Homesickness in asylum seekers: The role of mental health and migration-related factors - Rosner, Rita; Hagl, Maria; Bücheler, Leonie; Comtesse, Hannah (Frontiers in Psychiatry, 2022)
Background: While homesickness in refugees is a recurring theme in clinical practice, respective research in this population is scarce. The Utrecht Homesickness Scale (UHS) allows distinguishing between certain aspects of homesickness, namely genuine separation distress like missing family and friends or yearning for home on the one side and problems regarding adjustment to the new situation on the other; so far, the instrument was applied mainly in samples of university students, and never in refugees. Objective: We aimed to explore homesickness in a refugee population and its association with mental health symptoms and migration-related factors. In addition, we wanted to evaluate the UHS’s factor structure in a sample other than students. Methods: Individuals from different countries (N = 99) seeking asylum in Germany were assessed for homesickness, migration-related variables (e.g., number of losses and stage of the asylum proceedings), and mental health symptoms (symptoms of depression, posttraumatic stress and prolonged grief). After exploratory factor analysis, standardized mean factors scores were fed into subsequent correlational and regression analyses to identify the most prominent predictors of homesickness scores. Results: The participants showed substantial levels of homesickness. We found a three-factor solution that implied distinct factors regarding 1) adjustment difficulties and loneliness, 2) ruminations about home, and 3) missing family and/or friends. The total homesickness score was associated with mental health but regression analyses with the three mean factor scores showed differential associations with mental health and migration-related variables. While adjustment difficulties and loneliness were – besides time since arrival in Germany – associated with mental health problems (depressive and posttraumatic stress symptoms), ruminating about home was predicted by migration-related variables (number of losses and asylum status). For the factor scores regarding missing family and/or friends, the regression model was not significant. Conclusion: The assessment of homesickness in refugee populations is feasible and of clinical importance, especially when distinguishing between separation distress and difficulties with adjusting to the new situation.